Altered relationship between R-R interval and heart rate variability in overtrained endurance athletes - Kiviniemi, A. M.; Tulppo, M. P.; Hautala, A. J.; Vanninen, E.; Uusitalo, A. L. T. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
The correlation between R-R interval length (RRi) and vagally mediated heart rate variability (HRV) varies in young healthy subjects within 24-hour recording (R²: 0.31 - 0.97, Kiviniemi et al., 2004). It is not known whether overtraining syndrome (OT) affects this relationship. Thus, the aim of the present study was to assess the relationship between RRi and HRV over 24-hour recording among OT and control endurance athletes. Methods: Ambulatory 24-h ECG monitoring was performed for 9 OT (age: 28±7 years, 5 women) and 10 control endurance athletes (age: 27±6 years, 5 women). Overtrained athletes 1) had suffered from an unexplained long-term decrement in physical performance and fatigue, the symptoms being continued even after a recovery time of weeks to months, 2) were otherwise healthy, and 3) had a suitable training history for overtraining (Uusitalo et al. 2006). Ambulatory 24-h ECG monitoring was successfully repeated for 8 OT and 10 control athletes after 6 months. The power of low (LF, 0.04-0.15 Hz) and high frequency (HF, 0.15-0.4 Hz) oscillations of RRi were analyzed in 5-min epochs over the whole 24-hour recording. The 5-min values of HF power were transformed into natural logarithm (ln) and plotted against corresponding mean RRi. Due to the expected saturation of HRV at time of long mean RRi, quadratic regression was performed between RRi and HFln to obtain R² between these measures separately for each subject. Results: The mean RRi, HFln and LFln were similar between OT and control athletes (865±73 and 867±79 ms; 7.4±0.6 and 7.2±0.8 ln ms²; 7.6±0.6 and 7.7±0.5 ln ms², respectively, p=ns for all). LF/HF-ratio tended to be lower in OT compared with control athletes (1.2±0.3 vs. 1.8±0.8, p=0.063). The R² between RRi and HFln was higher in OT athletes compared with controls (0.87±0.04 vs. 0.78±0.11, p=0.031). This difference was vanished 6 months later (0.78±0.12 and 0.78±0.07, respectively, p=ns). Discussion: The overtraining strengthens the relationship between RRi and vagally mediated HRV without altering the mean RRi and HRV in endurance athletes. This indicates prevailing RRi being more tightly controlled by vagal activity in overtrained athletes compared with control athletes. Lower correlation between RRi and HRV in control athletes manifests other mechanism, potentially sympathetic activity as suggested by slightly higher LF/HF-ratio, affect the prevailing RRi more in non-OT than in OT athletes.